Meningkatkan Kompetensi Dosen melalui Pelatihan Pembuatan akun Sinta dan Google Scholar untuk Dosen Tetap STITNU Sakinah Dharmasraya - Fitri, Nidya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2021)
The competence of writing in reputable journals is a part of lecturers' competence in fulfilling the lecturers' duties in tri dharma college. The problem of lecturers at STITNU Sakinah Dharmasraya is that they do not yet have adequate knowledge to create the sinta and google scholar accounts needed to produce research. The results of the study were published online. This research aims to describe training of creating a sinta account and google scholar account to improve the writing ability of lecturers in STITNU lecturer Sakinah Dharmasraya. This training in creating sinta and google scholar accounts is conducted to enhance the competence of lecturer writing in the form of sinta account creation materials and google scholar accounts. Content material that is equipped for creating writing stages in reputable journals and how to imitate writing automatically in google scholar. The study results found that devotion in training positively impacted lectures, especially STITNU lecturer Sakinah Dharmasraya in carrying out an activity. Several lecturers evidence who have published their writings in reputable journals.